Help Desk System: a solution for the incident of management - Pérez Romero, Sadam (2024)
Objective. The handling of computer problems in an organization is complicatedwhen errors are frequent and quality standards are unmet. Technological tools are vital to address this. This research evaluated how a web system could improve the management of computer problems in the company Ecosem Morococha. Materials and methods. The study, quantitative, used an experimental approach and a sample of 50 items. It used the signing as a data collection technique and the registration signing as an instrument, being validated by experts and processed with the SPSS Statistics V.25 software. Results. The results showed an increase from 37.2 % to 85.9 % in the problem resolution rate and areduction from 38.90 % to 14.70 % in recidivism. Conclusions. It is concluded that the web system improves the management of computer problems in the company, contributing to more effective and timely management of incidents in Ecosem Morococha.